2012
DOI: 10.1111/j.1399-3062.2011.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Post renal transplantation Kaposi's sarcoma: a review of its epidemiology, pathogenesis, diagnosis, clinical aspects, and therapy

Abstract: PT-KS in renal transplant patients is an important problem specifically in southern Europe and the Middle East. In the majority of patients, the diagnosis based on clinical suspicion is always essential. Clinicians should bear in mind that PT-KS may threaten graft function and hence result in rejection complications. Appropriate management increases patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 38 publications
2
55
0
1
Order By: Relevance
“…In addition, previous reports showed that transplant recipients were much more susceptible to post‐transplantation cancers, including KS, than the general population . In the present study, a significantly elevated incidence of KS among transplant recipients (68.59 per 100 000 person‐years) was observed compared with the general population.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, previous reports showed that transplant recipients were much more susceptible to post‐transplantation cancers, including KS, than the general population . In the present study, a significantly elevated incidence of KS among transplant recipients (68.59 per 100 000 person‐years) was observed compared with the general population.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, the incidence of KS is 400–500 times higher among such patients than the general population [17]. This may be due to reactivation of latent HHV-8 virus or perhaps through acquisition of the virus from the donor organ [18]. However, certain immunosuppressants may be less likely to put patients at risk for iatrogenic KS.…”
Section: The Four Epidemiological Forms Of Kaposi’s Sarcomamentioning
confidence: 99%
“…Kaposi's sarcoma (KS) is a low-grade mesenchymal angioproliferative disorder occurring most commonly in immunocompromised individuals, such as human immunodeficiency virus (HIV)-infected patients or organ transplant recipients (1). KS is caused by the lytic replication of human herpesvirus type 8 (HHV-8/Kaposi's sarcoma-associated herpesvirus).…”
Section: Introductionmentioning
confidence: 99%